Nano-porous Co3Ti / Co composite electrode and preparation method and application thereof
The nanoporous Co3Ti/Co composite electrode was prepared by alloying method and chemical dealloyment method, which solved the problems of high cost and unstable structure of precious metal platinum catalysts, achieved efficient hydrogen evolution reaction performance, and provided a material basis for industrial water electrolytic cells.
Patent Information
- Application Number
- CN202411844823.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-12-16
AI Technical Summary
In the prior art, precious metal platinum, as a catalyst, has problems such as high cost, unstable structure and complex preparation processes, and is difficult to be applied to industrial water electrolytic cells on a large scale.
Nanoporous Co3Ti/Co composite electrodes were prepared by alloying method and chemical dealloyment method, and the hydrolysis intermediates were adsorbed by the characteristics of Co and Ti sites to improve the kinetics of the hydrogen evolution reaction.
It achieves efficient hydrogen evolution reaction performance, improves the specific surface area and electron transport capacity of the electrode material, and provides a material basis for large-scale hydrogen production of industrial water electrolytic cells.
Smart Images

Figure CN119392284A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalysts, and in particular to a nanoporous Co3Ti / Co composite electrode and a preparation method and application thereof. Background Art
[0002] Hydrogen energy is a clean and efficient secondary energy source. The most promising way to produce hydrogen is to drive the electrocatalytic water splitting reaction, which is generated by intermittent renewable energy sources such as solar energy and wind energy. The conversion and utilization of electrical energy and chemical energy is achieved through a water cycle with zero carbon emissions. The hydrogen evolution reaction (HER) at the cathode and the oxygen evolution reaction (OER) at the anode of the water splitting reaction both occur at the solid-liquid-gas interface of the electrode system. The reaction rate depends on the mass transfer process of the electrolyte and gas in the electrode pores, the electron transport process between the catalytic active phase and the current collector, and the redox reaction at the catalytic active phase / electrolyte interface. At present, the precious metal platinum is the HER electrode material with the highest intrinsic catalytic activity. Although structural nano-sizing can improve the utilization rate of precious metals, it is difficult to be applied to industrial water electrolysis cells on a large scale due to its low abundance and high price. Therefore, exploring non-precious metal-based electrode materials with low price, stable structure, simple preparation process, large specific surface area, high intrinsic catalytic activity, and both electron transport and mass transfer capabilities is the key to improving the performance of water splitting reactions and promoting the application of water electrolysis cells. Intermetallic compounds with a clear atomic structure have a variety of active site centers, and the adsorption energy of active sites to reaction intermediates can be regulated by electron transfer generated by the difference in electronegativity between different elements. In addition, intermetallic compounds have intrinsic thermodynamic stability due to their ordered crystal structure, which can increase the service life of electrode materials. Based on the above considerations, the present disclosure proposes a nanoporous Co3Ti / Co composite electrode and its preparation method and application. Summary of the invention
[0003] In order to overcome the above-mentioned deficiencies of the prior art, the present disclosure provides a nanoporous Co3Ti / Co composite electrode and a preparation method and application thereof.
[0004] According to a first aspect of the present disclosure, a method for preparing a nanoporous Co3Ti / Co composite electrode is provided, characterized in that it comprises the following steps:
[0005] a. Cleaning the metal: Soak and clean the high-purity Co and Ti metal sheets with acetone and dilute hydrochloric acid in turn, then use a dilute NaOH solution to corrode the oxide on the surface of the Al metal sheet, and then use ultrapure water to clean the Co, Ti, and Al metal sheets for several times, and then place the cleaned Co, Ti, and Al metal sheets in a vacuum drying oven to dry for later use;
[0006] b. Melting alloy ingots: weigh the Co, Ti, and Al washed with ultrapure water according to the atomic ratio of 22:8:70, and the total mass of the above metals is 10-12 g; place the weighed metals in an arc furnace, melt the alloy under an argon atmosphere, and arc melt for 6-10 times to obtain an alloy ingot with uniform alloy composition; wait for the alloy ingot to cool to room temperature, take out the alloy ingot, and the alloy ingot is silvery white;
[0007] c. Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size of less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification device, heating it to 1400°C under an argon atmosphere, with a heating rate of 10°C / min, keeping it at a preset insulation temperature for 15 minutes, stretching the small alloy ingot at a preset stretching speed, and the stretching stroke is 9 cm; after the stretching is completed and the temperature drops to room temperature, taking out the small alloy ingot, the small alloy ingot has a columnar appearance with a diameter of 1 cm;
[0008] d. Preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes of a preset size;
[0009] e. Chemical dealloying: The alloy disc is placed in a 6M KOH solution saturated with N2 at a preset corrosion temperature for corrosion. After a certain period of corrosion, when no bubbles are generated on the surface of the alloy disc, the alloy disc is washed with ultrapure water for multiple times to obtain a nanoporous Co3Ti / Co composite electrode.
[0010] Preferably, the precursor alloy composition of the alloy ingot in step b is Co 22 Ti8Al 70 (at%).
[0011] Preferably, in the preparation of the columnar alloy by the directional solidification method described in step c, the preset holding temperature is 1400° C., and the preset stretching speed is 100 μm / s.
[0012] Preferably, the alloy disc described in step d has a diameter of 1 cm and a thickness of 400 μm after cutting.
[0013] Preferably, in step e, the alloy disc is placed in a 6M KOH solution saturated with N2 at 70° C., and the corrosion time is 8 hours.
[0014] According to a second aspect of the present disclosure, a nanoporous Co3Ti / Co composite electrode is provided.
[0015] According to a third aspect of the present disclosure, there is provided an application of a nanoporous Co3Ti / Co composite electrode, characterized in that the composite electrode is used as a hydrogen evolution reaction electrode.
[0016] The principle of the disclosed technical solution is:
[0017] The composite electrode material is prepared by alloying and dealloying. First, metal Co, Ti, and Al are smelted into Co 22 Ti8Al 70 The alloy ingot is then stretched into an alloy column using a directional solidification device, and then cut into thin sheets using a wire cutter. 13 The Al-containing intermetallic compound is then corroded away with alkali solution by chemical dealloying to form a Co3Ti / Co intermetallic compound / metal composite electrode with a dual-mode pore structure.
[0018] The beneficial effects of the disclosed technical solution are:
[0019] The Co3Ti intermetallic compound disclosed in the present invention is seamlessly integrated on the nanoporous Co ligament, and the dual-mode pore structure increases the specific surface area of the electrode material, improves the mass transfer and electron transport capacity of the electrolyte. The Co and Ti sites in the intermetallic compound are respectively conducive to the adsorption of *H and *OH intermediates, thereby promoting the dissociation of water and the adsorption / desorption process of *H, and improving the kinetics of the alkaline hydrogen evolution reaction. The experimental results confirm that the electrode has excellent hydrogen evolution reaction performance, providing a material basis for large-scale hydrogen production applications in water electrolysis cells. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The above and other features, advantages and aspects of the embodiments of the present disclosure will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. The accompanying drawings are used to better understand the present solution and do not constitute a limitation of the present disclosure. In the accompanying drawings, the same or similar reference numerals represent the same or similar elements, among which:
[0021] Figure 1 , a scanning electron microscope (SEM) image of the nanoporous Co3Ti / Co composite electrode of the embodiment of the present disclosure;
[0022] Figure 2 , transmission electron microscope (HRTEM) image of the nanoporous Co3Ti / Co composite electrode of the embodiment of the present disclosure;
[0023] Figure 3 , Energy Dispersive Spectroscopy (EDS) diagram of the nanoporous Co3Ti / Co composite electrode of the embodiment of the present disclosure;
[0024] Figure 4 , X-ray diffraction (XRD) pattern of the nanoporous Co3Ti / Co composite electrode of the embodiment of the present disclosure;
[0025] Figure 5, polarization curve of hydrogen evolution reaction of nanoporous Co3Ti / Co composite electrode in 1M KOH electrolyte of the embodiment of the present disclosure;
[0026] Figure 6 , Tafel diagram of hydrogen evolution reaction of nanoporous Co3Ti / Co composite electrode of the embodiment of the present disclosure;
[0027] Figure 7 , the impedance spectrum of the nanoporous Co3Ti / Co in 1M KOH electrolyte according to the embodiment of the present disclosure;
[0028] Figure 8 , the stability of the hydrogen evolution reaction of the nanoporous Co3Ti / Co in the embodiments of the present disclosure. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the embodiments of the present disclosure clearer, the technical solution in the embodiments of the present disclosure will be clearly and completely described below in conjunction with the drawings in the embodiments of the present disclosure. Obviously, the described embodiments are part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure.
[0030] Example 1
[0031] A method for preparing a nanoporous Co3Ti / Co composite electrode, the steps are as follows:
[0032] 1) Cleaning the metal: soak and clean the high-purity Co and Ti metal sheets with acetone and dilute hydrochloric acid in turn, etch the oxide on the surface of the Al metal sheet with a dilute NaOH solution, then wash the Co, Ti, and Al metals with ultrapure water for multiple times, and dry them in a vacuum drying oven for 8 hours;
[0033] 2) Melting alloy ingot: Weigh the Co, Ti, and Al metals washed with ultrapure water according to the atomic ratio of Co, Ti, and Al of 22:8:70, weigh 3.63g of Co sheet, 1.07g of Ti sheet, and 5.30g of Al sheet. Place the weighed metals in an arc furnace, melt the alloy under an argon atmosphere, and start arc melting for 6 to 10 times to achieve uniformity of alloy composition; wait for the metal ingot to cool to room temperature, take out the alloy, the alloy is silvery white, and the composition of the alloy ingot is Co 22 Ti8Al 70 (at%);
[0034] 3) Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size of less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification device, heating it to 1400°C in an argon atmosphere at a heating rate of 10°C / min, keeping it at 1400°C for 15 minutes, stretching the alloy at a speed of 100 μm / s, and stretching the stroke of 9 cm; after the stretching is completed and the temperature drops to room temperature, taking out the small alloy ingot, the small alloy ingot has an appearance of a column with a diameter of 1 cm;
[0035] 4) preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes with a diameter of 1 cm and a thickness of 400 μm;
[0036] 5) Preparation of porous electrode material by chemical dealloying: The alloy disc was placed in a 6M KOH solution saturated with N2 at 70°C for corrosion. After 8 hours, when no bubbles were generated on the surface of the alloy disc, the alloy disc was washed with ultrapure water for multiple times to obtain a nanoporous Co3Ti / Co composite electrode material.
[0037] The morphology and structure characterization results of the composite electrode materials are as follows:
[0038] Figure 1 This is a scanning electron microscope image of nanoporous Co3Ti / Co. The electrode has a dual-mode pore structure with a large pore size of about 200nm. Figure 2 It shows that the pore size is about 3nm, the large pores are conducive to the mass transfer of electrolyte and gas molecules, the small pores can increase the specific surface area of the electrode material and improve the utilization of active sites, and the three-dimensional interconnected Co network promotes electron transfer during the hydrogen evolution reaction. Figure 3 The results show that the atomic ratio of Co, Ti and Al in nanoporous Co3Ti / Co is 81:13:6. Figure 4 In the XRD spectrum, the characteristic peaks of 41.6°, 44.3°, 47.4°, and 75.9° correspond to the (100), (002), (101), and (110) crystal planes of Co, respectively, and the characteristic peaks of 43.5°, 50.6°, and 74.2° correspond to the (111), (200), and (220) of Co3Ti, respectively, proving that the electrode is composed of Co and Co3Ti intermetallic compounds.
[0039] Example 2
[0040] The hydrogen evolution reaction performance of the composite electrode material obtained in Example 1 was tested in a three-electrode system. In 1M KOH, the nanoporous Co3Ti / Co composite electrode material was used as the working electrode, the Ag / AgCl electrode was used as the reference electrode, and the carbon rod was used as the counter electrode. The specific test process was as follows:
[0041] 1) In the voltage range of 0 to -0.15 V (relative to the reversible hydrogen electrode), the -1 The polarization curve of hydrogen evolution reaction was tested at a scanning speed of
[0042] 2) Test its impedance spectrum at -0.1V, set the frequency to 10mHz~100kHz, and set the amplitude to 5mV;
[0043] 3) The stability of the nanoporous Co3Ti / Co composite electrode was tested at a voltage of -0.1 V (relative to the reversible hydrogen electrode) for 1000 hours.
[0044] The characterization results of the hydrogen evolution reaction performance of the nanoporous Co3W-WNi4 / Ni electrode material are as follows:
[0045] Figure 5 The polarization curves of the hydrogen evolution reaction of the nanoporous Co3Ti / Co intermetallic compound / metal composite electrode and the nanoporous Co single metal electrode were compared. The Co3Ti / Co electrode only needs an overpotential of ~120mV to drive 2A cm -2 The current density is much lower than the overpotential of Co electrode (~360mV). Figure 6 As shown in Figure 2, the Tafel slope of the nanoporous Co3Ti / Co electrode is as low as ∼33 mV dec. -1 , which is significantly lower than that of Co electrode materials, indicating that Co3Ti / Co electrode has excellent hydrogen evolution reaction performance. Figure 7 As shown in Figure 2, the charge transfer resistance of the nanoporous Co3Ti / Co electrode is much smaller than that of the nanoporous Co electrode, which once again proves that the nanoporous Co3Ti / Co electrode has fast reaction kinetics. In addition, the stability of the electrode was tested at a potential of -0.1V (relative to the reversible hydrogen electrode), as shown in Figure 2. Figure 8 As shown in Figure 2, the generated current density can remain stable at ∼1.3 A cm for 1000 hours. -2 , indicating that the nanoporous Co3Ti / Co electrode material has excellent stability in hydrogen evolution reaction. This is because the nanoporous structure of the electrode is stable, and the intermetallic compound Co3Ti nanoparticles are seamlessly anchored on the strong Co ligaments. The coherent interface formed between Co3Ti and Co ligaments further enhances the service performance of the electrode.
[0046] In summary, the Co3Ti / Co intermetallic compound disclosed in the present invention is seamlessly integrated on the Co ligament with a dual-mode pore structure, with a large pore size of about 200nm and a small pore size of about 3nm. The dual-mode pore structure increases the specific surface area of the electrode material and improves the mass transfer and electron transport capacity of the electrolyte. The Co and Ti sites in the intermetallic compound are respectively conducive to the adsorption of *H and *OH intermediates, thereby promoting the dissociation of water and the adsorption / desorption process of *H, and improving the kinetics of the alkaline hydrogen evolution reaction. The experimental results of the electrochemical test show that the nanoporous Co3Ti / Co electrode has excellent hydrogen evolution reaction performance, which provides a material basis for large-scale hydrogen production in alkaline water electrolysis cells.
[0047] The above embodiments are preferred implementation modes of the present disclosure, but the implementation modes of the present disclosure are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present disclosure should be equivalent replacement methods and are included in the protection scope of the present disclosure.
Claims
1. A method for preparing a nanoporous Co3Ti / Co composite electrode, characterized in that: The following steps are involved: a. Cleaning the metal: Soak and clean the high-purity Co and Ti metal sheets with acetone and dilute hydrochloric acid in turn, then use a dilute NaOH solution to corrode the oxide on the surface of the Al metal sheet, and then use ultrapure water to clean the Co, Ti, and Al metal sheets for several times, and then place the cleaned Co, Ti, and Al metal sheets in a vacuum drying oven to dry for later use; b. Melting alloy ingots: weigh the Co, Ti, and Al washed with ultrapure water according to the atomic ratio of 22:8:70, and the total mass of the above metals is 10-12 g; place the weighed metals in an arc furnace, melt the alloy under an argon atmosphere, and arc melt for 6-10 times to obtain an alloy ingot with uniform alloy composition; wait for the alloy ingot to cool to room temperature, take out the alloy ingot, and the alloy ingot is silvery white; c. Preparation of columnar alloy by directional solidification method: grinding the oxide layer on the surface of the alloy ingot with sandpaper, cutting the alloy ingot into small alloy ingots with a size of less than 9 mm, placing the small alloy ingot in a crucible tube of a directional solidification device, heating it to 1400° C. in an argon atmosphere at a heating rate of 10° C. / min, keeping it at a preset insulation temperature for 15 min, stretching the small alloy ingot at a preset stretching speed, and stretching the small alloy ingot with a stretching stroke of 9 cm; After the stretching is completed and the temperature drops to room temperature, the small alloy ingot is taken out, and the small alloy ingot has a columnar appearance with a diameter of 1 cm; d. Preparing alloy flakes: cutting the columnar alloy ingots with a diamond wire cutting machine to obtain alloy flakes of a preset size; e. Chemical dealloying: The alloy disc is placed in a 6M KOH solution saturated with N2 at a preset corrosion temperature for corrosion. After a certain period of corrosion, when no bubbles are generated on the surface of the alloy disc, the alloy disc is washed with ultrapure water for multiple times to obtain a nanoporous Co3Ti / Co composite electrode.
2. The method for preparing the nanoporous Co3Ti / Co composite electrode according to claim 1, characterized in that: The precursor alloy composition of the alloy ingot in step b is Co 22 Ti8Al 70 (at%).
3. The method for preparing the nanoporous Co3Ti / Co composite electrode according to claim 1, characterized in that: In the preparation of columnar alloy by directional solidification method described in step c, the preset holding temperature is 1400° C., and the preset stretching speed is 100 μm / s.
4. The method for preparing the nanoporous Co3Ti / Co composite electrode according to claim 1, characterized in that: The alloy disc described in step d has a diameter of 1 cm and a thickness of 400 μm after cutting.
5. The method for preparing the nanoporous Co3Ti / Co composite electrode according to claim 1, characterized in that: In step e, the alloy disc is placed in a 6M KOH solution saturated with N2 at 70° C., and the corrosion time is 8 hours.
6. A nanoporous Co3Ti / Co composite electrode obtained according to the preparation method according to any one of claims 1 to 5.
7. The use of the nanoporous Co3Ti / Co composite electrode according to claim 6, characterized in that: The composite electrode is used as a hydrogen evolution reaction electrode.
Citation Information
Patent Citations
Aluminum-doped three-dimensional nano-porous metal sulfide hydrogen evolution electrode preparation and application methods
CN109055973A
Method for preparing Ti-Cu-Ni porous material from amorphous alloy and application of Ti-Cu-Ni porous material
CN111041303A
Nano-porous Co3W-WNi4 / Ni composite electrode and preparation method and application thereof
CN118222875A
Preparation method of cobalt-doped three-dimensional nano-porous nickel-based compound hydrogen evolution electrode
CN118241240A
Cited By
Nano-porous NiFeCoCuCrMn / Al3 (NiFeCoCuCrMn) 2 composite electrode as well as preparation method and application of nano-porous NiFeCoCuCrMn / Al3 (NiFeCoCuCrMn) 2 composite electrode
CN119433574A
Nanoporous NiFeCoCuCrMn / Al3(NiFeCoCuCrMn)2 composite electrode and preparation method and application thereof
CN119433574B